The efficacy of Radial and Focused Extracorporeal Shock-Wave Therapies in the Treatment of Subacute Coccydynia According to Age and Body Mass Index - Volkan Sah (Van Tıp Dergisi, 2023)
INTRODUCTION: The aim of this study is to investigate the effects of Radial Extracorporeal Shock Wave Therapy (r-ESWT) and Focused ESWT (f-ESWT) methods in the treatment of subacute coccydynia according to age and BMI. METHODS: Sixty patients were randomized into the three ESWT groups (Radial, Focused, Sham). All patients were evaluated with Visual Analog Scale (VAS) and Oswestry Disability Index (ODI) before treatment, right after 4 sessions of treatment (4 weeks), 1 month after the end of treatment (8th week), and 3 months after the end of treatment (16th week). RESULTS: Compared with baseline, the mean VAS scores of patients aged 18-35 showed a statistically significant decrease in the 4th week only in r-ESWT group (p<0.05). VAS scores at week 16 in the 18-35 age range decreased more in the r-ESWT group than in the f-ESWT group (p>0.05). The 16th week ODI scores decreased more in the r-ESWT group than in the f-ESWT group at the ages of 18-35, and in the f-ESWT group at the ages of 36-50 compared to the r-ESWT group (p>0.05 for both). While VAS and ODI scores at week 16 decreased more in the r-ESWT group in normal weight patients, these two scores decreased more in the r-ESWT group in overweight/obese patients at the same week (p>0.05). DISCUSSION AND CONCLUSION: The r-ESWT could be preferable in the early adulthood (18-35 ages) and normal weight patients (BMI <25) and the f-ESWT could be preferable in the ages of middle adulthood (36-50) and overweight/obese patients (BMI ≥25) in the treatment of coccydynia.